Changes in saxitoxin-production through growth phases in the metaphytic cyanobacterium Scytonema cf. crispum. (1st September 2015) - Harland, Francine; Wood, Susanna A.; Broady, Paul; Williamson, Wendy; Gaw, Sally
Abstract: The cyanobacterium Scytonema cf. crispum produces a range of saxitoxins. Previous studies on other saxitoxin-producing cyanobacteria have shown that toxin production can vary throughout the growth cycle. Monitoring cyanotoxin-production in S. cf. crispum is challenging because it is metaphytic and has a very slow growth rate (ca. 6 months to reach stationary phase). In this study, a new method was developed to track growth and toxin production in S. cf. crispum . Samples were collected once a week for 131 days, and cell concentrations and saxitoxin quotas determined. Cells in the lag and exponential growth phases had significantly ( P < 0.05) higher saxitoxin quotas (162 ± 37 fg cell −1 and 139 ± 32 fg cell −1, respectively) than the stationary phases (83 ± 19 fg cell −1 ). Extracellular saxitoxin concentrations were present at low concentrations (2–16 ng mL −1 of culture medium) throughout the experiment. The proportion of extracellular saxitoxin to total saxitoxin decreased throughout the experiment. New knowledge on growth and saxitoxin variability will assist in improving monitoring, risk assessment and management of this species. Highlights: A method was developed to track growth and toxin production in metaphytic cyanobacterium. Scytonema cf. crispum . Saxitoxin quotas were significantly higher in the lag and exponential phase, compared to the stationary phase. Extracellular saxitoxin concentrations were low throughout the experiment. These data will assist in improving monitoring and risk assessment related to this species.